Os novos espaços de acumulção do Grupo Votorantim - Santos, Leandro Bruno [UNESP] (My University, 2010)
This article aims to getting at the recent changes in Brazilian industrial capitalism, especially the expansion of companies and business groups abroad. The analyzed theme is the Votorantim Group, one of the most important groups in the country and Latin America. The Group acts in several branches of the economy and it has recently invested in the acquisition of foreign companies in different business and countries. In this article, the theories of internationalization of companies and business groups and the path of the Votorantim Group are focused - from its origin to productive internationalization. The secondary data were compiled from annual reports of the group, specialized magazines and newspapers.
The new spaces of accumulation of the Votorantim Group
Keywords: Brazil; Globalization; Production of space; Territorial dynamics; Votorantim Group; business development; globalization; industrial development; industrial performance; theoretical study; Latin America